Trends of tourism development in Ukraine - Skril, Iryna (Human Geography Journal, 2017)
The article is devoted to the actual subject - features development of tourism inUkraine. Tourism inUkrainelegally declared as a priority of national culture and economy. The promotion ofUkraineas a European state requires the development of tourism industry. The modern concept of leisure activities organization leads to increased demand for tourism in those regions, which have the cultural, social, household identity of the nation, local community. These areas are presented in the most regions ofUkraine. Due to the wealth of historical, cultural, recreational, social and economic resourcesUkrainehas all essential prerequisites for intensive tourism development. Tourism plays an important role in regional development. Currently, most researches are aimed at economic aspects of development, which are usually associated with external (international) tourism. However not enough attention were paid to social and environmental aspects of domestic tourism, which may become an important tool for spiritual revival, patriotic education, formation of ecological thinking and future mentality of the Ukrainian society. In the development of tourism inUkrainethere are some features: changing in the ratio of internal and external tourism in favor of external, a small number of foreign tourists, the gradual reduction in the number of citizens covered by domestic tourism. In 2015 the tourist flow was at the level of 2000 and amounted into 2,02 million people. There was a reduction compared to 2013 by almost 40%. Although the highest rates of reduction (30%) occurred in 2014, and 10% - in 2015. So the rate of decrease in tourist flow slowed. The number of foreign tourists significantly reduced to a record 0.75% of the total number of travelers. On the contrary, the number of citizens ofUkraine, which travelled abroad remains very high and exceeds 80%. The number of domestic tourists remains at the level of 17%. Unfortunately, the negative trends in domestic tourism and excursion activity were caused by both economic and political troubles of last three years.